2014
DOI: 10.1016/j.lfs.2014.03.029
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and obesity are significant risk factors for morning hypertension: From Ibaraki Hypertension Assessment Trial (I-HAT)

Abstract: Diabetic or obese patients frequently have morning HT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…We also notice that diabetes frequently precedes coronary heart disease, 33 chronic kidney disease 34 and hypertension, 35 which are major risk factors and account for the majority of HF cases, 5 further explaining the close relationship between DM and HF observed in epidemiological studies.…”
mentioning
confidence: 64%
“…We also notice that diabetes frequently precedes coronary heart disease, 33 chronic kidney disease 34 and hypertension, 35 which are major risk factors and account for the majority of HF cases, 5 further explaining the close relationship between DM and HF observed in epidemiological studies.…”
mentioning
confidence: 64%
“…26 In contrast, observational evidence revealed that diabetic or obese patients frequently have morning hypertension. 27 A case-control study demonstrated that diabetes was a significant risk factor for hypertension and that diabetes positively interacted with hypertension. 28 Therefore, we hypothesized that hypertension and diabetes are causally linked.…”
Section: Causal Relationships Between Chronic Diseases Hypertension A...mentioning
confidence: 99%
“…The Ibaraki Hypertension Assessment Trial (I-HAT) examined the home BP of 2,554 hypertensive patients including type 2 diabetes patients (20%) who were undergoing hypotensive therapy and found that as glucose tolerance gradually worsened, from normal, abnormal, and ultimately to diabetes, the subjects' early morning home BP became significantly higher, from 134.1 and 135.4 mmHg to 137.5 mmHg. Their frequency of morning hypertension ( > 135/ 85 mmHg) also rose significantly, from 53.4 and 55.6 to 66.4% [55]. Furthermore, despite undergoing treatment for hypertension,~60% of diabetic patients still manifested morning hypertension and eventually developed microangiopathy and cerebrovascular disorders.…”
Section: Abnormal Circadian Blood Pressure Variations In Diabetic Patmentioning
confidence: 99%